Extrusion based 3D printing as a novel technique for fabrication of oral solid dosage forms - Khaled, Shaban (2016)
Extrusion based three dimensional (3D) printing is defined as a process used to make a 3D object layer by layer directly from a computer aided device (CAD). The application of extrusion based 3D printing process to manufacture functional oral solid tablets with relatively complex geometries is demonstrated in this thesis. In Chapter 3 the viability of using a basic desktop 3D printer (Fab@Home) to print functional guaifenesin bilayer tablets (GBTs) is demonstrated. Guaifenesin is an over the counter (OTC) water soluble medicine used as expectorant for reduction of chest congestion caused by common cold and infections in respiratory system. The bilayer tablets were printed using the standard pharmaceutical excipients; hydroxypropyl methyl cellulose (HPMC) 2208, 2910, sodium starch glycolate (SSG), microcrystalline cellulose (MCC) and polyacrylic acid (PAA) in order mimic the commercial model formulation (Mucinex®) guaifenesin extended-release bilayer tablets. The 3D printed guaifenesin bilayer tablets (GBTs) were evaluated for mechanical properties as a comparison to the commercial GBTs and were found to be within acceptable range as defined by the international standards stated in the USP. Drug releases from the 3D printed GBTs were decreased as the amount of HPMC 2208 increased due to the increased wettability, swelling properties and gel barrier formation of the HPMC. The 3D printed GBTs also showed, as required, two release profiles: immediate release (IR) from the top layer containing disintegrants; SSG and MCC and sustained release (SR) profile from the lower layer containing HPMC 2208. The kinetic drug release data from the 3D printed and commercial GBTs were best modelled using the Korsmeyer–Peppas model with n values between 0.27 and 0.44. This suggests Fickian diffusion drug release through a hydrated HPMC gel layer. Other physical characterisations: X-Ray Powder Diffraction (XRPD), Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR-FTIR), and Differential Scanning Calorimetry (DSC) showed that there was no detectable interaction between guaifenesin and the used excipients in both 3D printed and commercial GBTs. A more complex printer (RegenHu 3D bioprinter) was subsequently used to print complex multi-active tablets containing captopril, nifedipine, and glipizide as a model therapeutic combination. These drugs are frequently used to treat hypertension and diabetes mellitus. The 3D printed tablets were evaluated for drug release and showed that captopril was released by osmosis through permeable cellulose acetate (CA) film and both glipizide and nifedipine were released by diffusion through the hydrophilic HPMC 2208 matrix. According to XRPD and ATR-FTIR results, there was no detectable interaction between the actives and the used excipients. In the final experimental chapter, a combined treatment regimen: atenolol, ramipril, hydrochlorothiazide (anti-hypertensive medications), pravastatin (cholesterol lowering agent), and aspirin (anti-platelets) were printed into more complex geometry (polypill) using the RegenHu 3D bioprinter. This combined drug regimen is manufactured by Cadila Pharmaceuticals Limited as a capsule formulation under the trade name of Polycap™ and is currently the only polypill formulation commercially available and is used to treat and prevent cardiovascular diseases. The printed polypills were characterized for drug release using USP dissolution testing and showed the intended immediate and sustained release profiles based upon the active/excipient ratio used. Aspirin and hydrochlorothiazide were immediately released after the polypill contacted the dissolution medium, and atenolol, ramipril, and pravastatin were released over a period of 12 hrs. XRPD and ATR-FTIR showed that there was no detectable interaction between the actives and the used excipients. In this work, extrusion based 3D printing technique was used to print oral solid dosage forms with complex and well-defined geometries and function. The technology of 3D printing could offer the opportunity to print oral tablets with high and precise drug dosing and controlled drug release profiles tailored for sub-populations or individuals. If the manufacturing and regulatory issues associated with 3DP can be resolved such personalised medicine delivered by 3D printing could improve patient compliance and provide more effective treatment regimes.